Teaching Public, Scientific Controversy: Genetically Modified Mosquitoes in the Technical Writing Classroom. (January 2019) - Phillips, Stephanie
The release of genetically modified mosquitoes in the Florida Keys is part of a public health initiative to limit the spread of infectious disease. The local debate over this proposed action provides a current case study of a public, scientific controversy in which citizens and officials disagree about what is best for the community. The case study challenges technical writing students to consider complex cultural circuits, or networks, that comprise a specific controversy. The students analyze the rhetorical situation, create new content that contributes to the ongoing discussion, and learn about audience through usability testing their multimodal projects.